Gluck - art and identity art and identity - De la Haye, Amy; Pel, Martin; Gluck 1895-1978 (Yale University Press, 2017)
Hannah Gluckstein (who called herself Gluck; 1895-1976) was a distinctive, original voice in the early evolution of modern art in Britain. This handsome book presents a major reassessment of Gluck's life and work, examining, among other things, the artist's numerous personal relationships and contemporary notions of gender and social history. Gluck's paintings comprise a full range of artistic genres...still life, landscape, portraiture...as well as images of popular entertainers. Financially independent and somewhat freed from social convention, Gluck highlighted her sexual identity, cutting her hair short and dressing as a man, and the artistis known for a powerful series of self-portraits that played with conventions of masculinity and femininity. Richly illustrated, this volume is a timely and significant contribution to gender studies and to the understanding of a complex and important modern painter
On the occasion of the exhibition 'Gluck: art and identity', Brighton Museum & Art Gallery, 18 November 2017 - 11 March 2018
Includes bibliographical references and index
Keywords: Gluck -- 1895-1978 -- Criticism and interpretation; Gluck -- 1895-1978; ART / Individual Artists / Monographs / bisacsh; ART / History / Modern (late 19th Century to 1945) / bisacsh; ART / Individual Artists / Monographs; ART / History / Modern (late 19th Century to 1945); Ausstellungskatalog -- Royal Pavilion, Art Gallery and Museums -- 18.11.2017-11.03.2018 -- Brighton